The midwife's Christmas wish [large type] - Bale, Leigh (Bale, Leigh. Secret Amish Babies Tale., 2021)
"When Amish midwife Lovina Albrecht finds an abandoned baby, she's determined to give the child a home for the holidays--even if doing so brings up difficult memories. But she's not prepared for her bishop to assign standoffish Jonah Lapp to help care for the little girl. As their temporary arrangement begins to feel like family, can they overcome old hurts to build a future?"--Back cover.